Loss of the arginine methyltranserase PRMT7 causes syndromic intellectual disability with microcephaly and brachydactyly. Issue 5 (30th November 2016) - Kernohan, K.D.; McBride, A.; Xi, Y.; Martin, N.; Schwartzentruber, J.; Dyment, D.A.; Majewski, J.; Blaser, S.; ,; Boycott, K.M.; Chitayat, D.
Abstract : Post‐translational protein modifications exponentially expand the functional complement of proteins encoded by the human genome. One such modification is the covalent addition of a methyl group to arginine or lysine residues, which is used to regulate a substantial proportion of the proteome. Arginine and lysine methylation are catalyzed by protein arginine methyltransferase (PRMTs) and protein lysine methyltransferase proteins (PKMTs), respectively; each methyltransferase has a specific set of target substrates. Here, we report a male with severe intellectual disability, facial dysmorphism, microcephaly, short stature, brachydactyly, cryptorchidism and seizures who was found to have a homozygous 15, 309 bp deletion encompassing the transcription start site of PRMT7, which we confirmed is functionally a null allele. We show that the patient's cells have decreased levels of protein arginine methylation, and that affected proteins include the essential histones, H2B and H4. Finally, we demonstrate that patient cells have altered Wnt signaling, which may have contributed to the skeletal abnormalities. Our findings confirm the recent disease association of PRMT7, expand the phenotypic manifestations of this disorder and provide insight into the molecular pathogenesis of this new condition. Abstract :